APLIKASI KODE ASCII TERHADAP ALAT KONTROL KENDARAAN PRIBADI - Muklas, Abdul Jalil; Habib, Bidya Nur; Widodo, Bagas Haryono (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Private vehicles such as motorcycle and car are very popular in our society. Besides used for transportation, they become a lifestyle too. Some of our people cannot have them. This difference has bad effects that gave birth to the chaos and crimes. This is caused by the jealousy factor. Based on that problems we are planning to make an equipment with ASCII code that can control and secure them from the distance, by SMS (Sort Message Send) through mobile phone. We expect to minimize the problems by using this equipment.